RAPID FATTENING OF WEANED LAMBS - ΚΑΛΑΪΣΑΚΗΣ Π.; ΠΑΠΑΔΟΠΟΥΛΟΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 1973)
In a series of experiments, conducted at the Agricultural College of Athens with crossbred lambs (Friessian X local Attica breed) aged 2 to 3 days, were studied the requirements in energy and digestible protein for the production of lambs slaughtered at 30 to 32 Kg live weight and having carcass quality similar to that of heavy weight milkfed lambs. It was found that this can be achieved with 30 days of feeding with milk substitute and a total intake of 50.000 starch units, 5 : 1 ratio of starch units to digestible protein until 11 weeks of age and 6 : 1 subsequently until the end of fattening period (15 weeks). A linear relationship was found to exist 1) between 10 week live weight and starch units or dry matter intake, 2) between 15 week live weight and starch units or dry matter intake and 3) between 10 and 15 week live weight. These relationships provide the ways to be followed for further study on the subject.